E-advertisment / Lee Huey Ling - Lee , Huey Ling (2006)
The E-advertisement is a web-based system that provides an easy and efficient way to access information for all the system users. This system is basically developed for those who do not have time to find the advertisements one by one on the traditional classified ads. E-advertisement's service is also available 24 hours per day throughout the year because it is available online. The objectives of the E-advertisement are able to let user to post advertisement online. User can post advertisements with picture base on the category and sub category. Besides that, user can search items faster and easier by entering keyword, category, location and price range. The Unified Software Development Process is used to develop the E-advertisement. The tools that I will use are the Microsoft Internet Information Server (IIS), Client/Server three-tier system architecture, Active Server Page (ASP), Microsoft SQL server 2000 as database, Macromedia Dream Weaver and Cascading Style Sheet (CSS) which I think that I can handle when developing the E-advertisement. Hence, to be a good and attractive online classified ads system, the E- advertisement will be produced to be a more efficient system which can satisfy user and administrator.